Synthesis of jatropha-oil-based polyester polyol as sustainable biobased material for waterborne polyurethane dispersion - Sundang, Murni; Nurdin, Nur Sjanrah; Saalah, Sariah; Singam, Yamunah Jaibalah; Osman Al Edrus, Syeed SaifulAzry; Ismail, Noor Maizura; Sipaut, Coswald Stephen; Abdullah, Luqman Chuah (Multidisciplinary Digital Publishing Institute, 2022)
The utilization of vegetable oil in the production of polymeric material has gained interest due to its proven ability to replace nonrenewable petroleum sources, as it is readily modified via chemical reaction to produce polyol and subsequently for polyurethane production. Jatropha oil (JO), a second-generation feedstock, is one of the suitable candidates for polyester polyol synthesis because it contains a high percentage of unsaturated fatty acids. In this study, jatropha-based polyester polyols (JOLs) with different hydroxyl values were successfully synthesized via a two-step method: epoxidation followed by oxirane ring-opening reaction. Ring-opening reagents; methanol, ethanol, and isopropanol were used to produce polyol with hydroxyl number of 166, 180, and 189 mg/KOH, respectively. All the synthesized JOLs exhibited a Newtonian to shear thinning behavior in the measured shear rate ranges from 10 to 1000 s−1 at 25 °C. The viscosity of a JOL ring-opened with methanol, isopropanol, and ethanol was 202, 213, and 666 mPa·s, respectively, at 20 °C and 100 s−1, which is within the range of commercially available polyols. Successively, the JOLs were reacted with isophorone diisocyanate (IPDI) to produce polyurethane prepolymer by utilizing 2,2-dimethylol propionic acid (DMPA) as an emulsifier. The prepolymer was then dispersed in water to produce a waterborne polyurethane dispersion. Colloidal stability of the jatropha-based polyurethane dispersions (JPUDs) were investigated by particle size analysis. A JPUD with a small particle size in the range of 6.39 to 43.83 nm was obtained, and the trend was associated with the soft segment of the polyol in the formulation. The zeta potentials of the JPUs ranged from −47.01 to −88.9 mV, indicating that all synthesized JPUs had high dispersity and stability. The efficient synthesis procedure, low cost, and excellent properties of the resulting product are thought to offer an opportunity to use jatropha oil as a sustainable resource for polyester polyol preparation.